1990
DOI: 10.1021/ma00210a006
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble copolymers. 31. Effects of molecular parameters, solvation, and polymer associations on drag reduction performance

Abstract: The relationships between drag reduction performance and polymer parameters including chemical structure, molecular weight, hydrodynamic volume, associations, and solvent nature were examined using synthetic water-soluble copolymers. Copolymer models were tailored to be systematically responsive to changes in electrolyte addition and included polyelectrolytes, polyampholytes, hydrophobically modified polymers, and uncharged, hydrophilic polymers. Commercial poly(ethy1ene oxide) (PEO) and copolymers of acrylami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 5 publications
1
39
0
Order By: Relevance
“…Coagulation and flocculation method is widely used for treating majority of industrial wastewaters [37,38]. Terephthalic acid is the main component in an alkali decrement wastewater, which was efficiently removed using ferric chloride in a high pH solution.…”
Section: Discussionmentioning
confidence: 99%
“…Coagulation and flocculation method is widely used for treating majority of industrial wastewaters [37,38]. Terephthalic acid is the main component in an alkali decrement wastewater, which was efficiently removed using ferric chloride in a high pH solution.…”
Section: Discussionmentioning
confidence: 99%
“…DR efficiency varies with polymer concentration, molecular weight, and chain length, whereas the coil dimension is considered to be as important as molecular weight [68,69]. McCormick et al [69] suggested that good DR can be achieved by low-molecular-weight polymers if their concentrations are high enough (Figure 14).…”
Section: Molecular Weight and Polydispersity Effectmentioning
confidence: 99%
“…The biodegradation resistance of these copolymers is enhanced because the altered molecular structures inhibit enzyme attack [Singh, 1995]. McCormick et al also reported that copolymers of PAM with polyelectrolytes showed better DR efficiency than that of PAM alone [McCormick et al, 1990;Mumick and McCormick, 1992]. McCormick et al also reported that copolymers of PAM with polyelectrolytes showed better DR efficiency than that of PAM alone [McCormick et al, 1990;Mumick and McCormick, 1992].…”
Section: Copolymersmentioning
confidence: 99%